The Mediating Role of Brand Image on Purchase Intention: An Analysis of Product Quality, Price, and Promotion - Permadi Hakim, Yundi; Pusriadi, Tommy; Lestono, Bowo (Yayasan Pendidikan Belajar Berdikari, 2024)
This research aims to examine the influence of product quality and promotion on purchase intention. Utilizing a quantitative approach, data were collected from a sample of 100 respondents through a structured questionnaire. The data were then analyzed using multiple regression analysis to determine the relationships between the variables. The findings reveal that product quality has a significant positive effect on purchase intention, with a coefficient of 0.422 and a p-value of 0.000, indicating that higher product quality leads to a higher intention to purchase. Conversely, promotion did not show a significant impact on purchase intention, with a coefficient of 0.183 and a p-value of 0.110. The model's R Square value of 0.427 suggests that 42.7% of the variance in purchase intention can be explained by product quality and promotion. The F-test result, with an F-value of 36.174 and a p-value of 0.000, confirms that the regression model is statistically significant. These findings suggest that while product quality is a crucial factor in driving purchase intention, promotion alone may not be sufficient. Companies are recommended to prioritize enhancing product quality to boost consumer purchase intentions. Further research should explore additional factors that could impact purchase intention to develop more comprehensive marketing strategies